2016
DOI: 10.3389/fnagi.2016.00165
|View full text |Cite
|
Sign up to set email alerts
|

Different Alterations of Cerebral Regional Homogeneity in Early-Onset and Late-Onset Parkinson's Disease

Abstract: HIGHLIGHTS Eighteen EOPD, 21 LOPD and 37 age-matched normal control subjects participated in the resting state fMRI scans.Age at onset of PD modulates the distribution of cerebral regional homogeneity during resting state.Disproportionate putamen alterations are more prominent in PD patients with a younger age of onset.Objective: Early-onset Parkinson's disease (EOPD) is distinct from late-onset PD (LOPD) as it relates to the clinical profile and response to medication. The objective of current paper is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…These are summarised briefly. Comparing early onset PD to late onset PD using ReHo, differences were found in the right putamen and left superior frontal gyrus ( Sheng et al, 2016 ). In PD patients suffering from pain resulting from the disease, a disconnection between right nucleus accumbens and left hippocampus as well as altered orbitofrontal and cerebellar fractional ALFF were revealed compared to PD patients without pain ( Polli et al, 2016 ).…”
Section: Evidence On Resting-state Fmri In Neurodegenerative Diseasesmentioning
confidence: 99%
“…These are summarised briefly. Comparing early onset PD to late onset PD using ReHo, differences were found in the right putamen and left superior frontal gyrus ( Sheng et al, 2016 ). In PD patients suffering from pain resulting from the disease, a disconnection between right nucleus accumbens and left hippocampus as well as altered orbitofrontal and cerebellar fractional ALFF were revealed compared to PD patients without pain ( Polli et al, 2016 ).…”
Section: Evidence On Resting-state Fmri In Neurodegenerative Diseasesmentioning
confidence: 99%
“…With the ReHo analysis, the dysfunction of neural synchronization in the cortico-striatalthalamo-cortical circuit (CSTS) (Zhang et al, 2015), visual processing circuit (Li et al, 2016), and emotional processing circuit (Hu et al, 2019) have been clarified in PD. In terms of age of onset, the synchronizations in both the right putamen and left superior frontal gyrus were different between EOPD and LOPD, and the ReHo values of the right putamen were negatively correlated with the Unified Parkinson's Disease Rating Scale (UPDRS) total scores in LOPD that indicated the distribution of cerebral ReHo was associated with onset-age (Sheng et al, 2016). Sheng et al's (2016) study also found higher ReHo values in the left inferior temporal gyrus in EOPD and suggested that further studies are needed to confirm these findings and effects on the emotion regulation in EOPD.…”
Section: Introductionmentioning
confidence: 99%
“…However, subject dropout led to fewer available subjects at each successive timepoint, with 33 subjects remaining at year 4. Though we have used more subjects than previous studies which have successfully detected associations between rs-fMRI and PD severity/progression with 39, 22, and even 17 subjects [6,5,36], we expect a larger dataset would likely increase the predictive power of the models. Furthermore, the group of 33 subjects at year 4 had earlier-stage disease (mean disease duration 532 ± 346 versus 770 ± 565 days, p = 0.03) compared to the original 82 subjects.…”
Section: Limitationsmentioning
confidence: 99%
“…Regional homogeneity (ReHo) quantifies the similarity of each voxel's activity with that of its neighbors [4]. ReHo in the cerebellum and lingual gyrus has been shown to be positively correlated with disease severity, while ReHo in the putamen is negatively correlated with Parkinson's disease severity [5,6]. Amplitude of low frequency fluctuation (ALFF) and its normalized form, fractional ALFF (fALFF), are measures of the power of the low frequency resting-state signals [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation